Lactoferrin as a Potential Immune Biomarker in Breast Milk Exposed to Secondhand Smoke: A Literature Review - Sarah Angelica W. Simamora; Artika Sri Wahyuni; Elffisa Eriani; Ario Sucipto; Nayla Khairani; Yadi Oktariansyah (BIOVALENTIA: Biological Research Journal, 2026)
Smoking remains prevalent in Indonesia and poses health risks to mothers and infants. Data from the Maternal and Perinatal Death Notification (MPDN) system indicate that maternal mortality increased to 4,129 cases in 2023 from 4,005 cases in the previous year. Although maternal mortality is multifactorial, this highlights the importance of reducing environmental risks such as secondhand smoke (SHS) exposure. SHS is common in household environments and may affect breastfeeding mothers and infants. Breast milk is the main source of infant nutrition and supports early immune protection. Lactoferrin, an iron-binding glycoprotein in breast milk, has antimicrobial, anti-inflammatory, and immunomodulatory functions. SHS-induced oxidative stress may damage the structural integrity of glycoproteins in breast milk, including lactoferrin, which can impair their immunological functions. This literature review aims to examine the potential role of lactoferrin as an immune biomarker in breast milk from mothers exposed to SHS. This study used a literature review approach by identifying, selecting, and synthesizing relevant scientific articles on SHS exposure, breast milk composition, lactoferrin, and infant immune protection based on predetermined inclusion criteria. The reviewed literature indicates that SHS exposure is associated with oxidative stress and inflammatory responses, which may interfere with lactation quality and alter immune-related glycoproteins in breast milk. Lactoferrin is considered a potential biomarker because it is related to antimicrobial activity, immune regulation, and infant protection against infection. This review concludes that reducing household SHS exposure is important to protect breastfeeding mothers and maintain breast milk immunological quality. Further empirical studies are recommended to examine the direct relationship between SHS exposure intensity and lactoferrin levels by considering lactation stage, maternal nutritional status, infant age, infection history, and breastfeeding patterns.